Plasma membrane topography governs the 3D dynamic localization of IgM B cell antigen receptor clusters - Deniz Saltukoglu; Buğra Özdemir; Michael Holtmannspötter; Ralf Reski; Jacob Piehler; Rainer Kurre; Michael Reth (2023)
Abstract B lymphocytes recognize bacterial or viral antigens via different classes of the B cell antigen receptor (BCR). Protrusive structures termed microvilli cover lymphocyte surfaces, and are thought to perform sensory functions in screening antigen‐bearing surfaces. Here, we have used lattice light‐sheet microscopy in combination with tailored custom‐built 4D image analysis to study the cell‐surface topography of B cells of the Ramos Burkitt's Lymphoma line and the spatiotemporal organization of the IgM‐BCR. Ramos B‐cell surfaces were found to form dynamic networks of elevated ridges bridging individual microvilli. A fraction of membrane‐localized IgM‐BCR was found in clusters, which were mainly associated with the ridges and the microvilli. The dynamic ridge‐network organization and the IgM‐BCR cluster mobility were linked, and both were controlled by Arp2/3 complex activity. Our results suggest that dynamic topographical features of the cell surface govern the localization and transport of IgM‐BCR clusters to facilitate antigen screening by B cells.